Decentralized Delivery of Financial Education : Evidence from a Country-Wide Field Experiment - Hakizimfura, Emmanuel; Randall, Douglas; Zia, Bilal (World Bank, Washington, DC, 2018)
Can financial education delivery be successfully decentralized? This paper studies a large-scale field experiment with 200 Savings and Credit Cooperative Associations (SACCOs) in Rwanda, and tests competing models of local financial education delivery. One-third of SACCOs, randomly selected, were invited to a comprehensive training-of-trainers (TOT) workshop and stipulated to send the SACCO manager, a loan officer, and a board member to be trained. Another one-third were invited to the same workshop, but allowed free selection of trainers. The latter resulted in significantly more community members and fewer loan officers being trained as trainers. Within a year, these trainers successfully disseminated content to 68,000 households, with higher session attendance in the autonomous selection group. Analysis from follow-up surveys finds stark differences in behavior change: recipients in the autonomous selection group show significant improvements in financial attitudes, rules of thumb, and planning, as well as budgeting and savings behaviors. In contrast, recipients in the fixed selection group show no significant improvements on any of the outcome measures. These results underscore the importance of community-led delivery of financial education programs.